Reality of cognitive empowerment for teachers of physical education in Baghdad - نجلاء دنيف عبد أ. م. د سحر حر مجيد (الرياضة المعاصرة)
The importance lies. Cognitive empowerment is a tool and a scientific approach that aims to make judgments about the extent to which the educational process achieves its goals and objectives, as cognitive empowerment is one of the main aspects of faculty members, as it represents an effective tool in developing and developing their capabilities. As for the research problem, it is worth noting that the topic of the study Cognitive empowerment is one of the modern administrative topics that have attracted the attention of students and researchers, as it is one of the desirable behaviors that schools seek to enhance among their members. The goal of the research was to build and apply the measure of cognitive empowerment for physical education teachers. As for the research community, it included the teaching of sports education in the directorates of education in the governorate of Baghdad, numbering (307) teachers and schools for the academic year 2020-2021. ) Including twenty-nine (29) criteria, while the most important recommendations were to benefit from the Moqati lists Ace of cognitive empowerment that has been reached in the preparation of training courses in continuing education centers in the directorates of education.